Bronchogenic carcinoma: Has the outlook changed? - F.I. Hashmi; M.J. Mpe (South African Family Practice)
Background: The purpose of the study was to determine the proportion of patients with bronchogenic carcinoma amenable to curative surgery at diagnosis.